Photovoltaic panels and planning in the UK - Brotas, Luisa (International Solar Energy Society, 2023)
Photovoltaic panels rights in planning are not clearly defined in the UK. There are also no accepted criteria to assess how much is considered an acceptable reduction of solar radiation being enjoyed previously. This has even resulted in legal challenges of planning decisions. Conversely, increased global awareness to the need to reduce carbon emissions, volatile energy prices and shortage of supply, have increased the appetite for the installation of PV panels to generate renewable energy locally. This paper presents a case study of a new development in a terrace house and assesses the impact on an existing PV panel installation on a neighbouring building. Three different methods are discussed and a further detailed method of assessment that better quantifies the impact loss of the PV panels is proposed. Its rationale could lead to more informed decisions made to new developments submitted for planning.